The impact of Transformational Leadership on employee performance during Covid-19: A literature review - Novita, Elvitria Intan; Meilani, Yohana Cahya F. Palupi (Institute of Computer Science (IOCS), 2023)
The performance of employees is crucial for the success in achieving the organization's targets. When employee performance is good, the organization's performance will also be good, and conversely, if employee performance is poor, the organization's performance will decline. Many factors can influence employee performance, one of which is the leadership style of the employee's leaders, which in this study is about transformational leadership. The role of transformational leadership includes providing inspiration and motivation for employees to develop themselves, ultimately leading to their best efforts. The purpose of this study was to review systematically the existing research on transformational leadership and its relation to performance. This study is a literature review that attempts to examine research related to the relationship between transformational leadership and employee performance. This study traced researches related to transformational leadership from 2013 to 2023. The findings obtained are that transformational leadership, through its four dimensions, can influence performance. This study will offer opportunities for further empirical research, related to other leadership style that can affect employee performance.